2022
DOI: 10.3389/fendo.2021.780392
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Clomiphene Citrate and Letrozole in Mild Ovarian Stimulation Versus Conventional Controlled Ovarian Stimulation Among POSEIDON Group 4 Patients

Abstract: This retrospective study assessed the effect of the co-administration of clomiphene citrate (CC) and letrozole in mild ovarian stimulation, compared to conventional regimens, among Patient-Oriented Strategies Encompassing Individualized Oocyte Number (POSEIDON) Group 4 patients. There were 114 POSEIDON Group 4 patients undergoing in vitro fertilization treatments with 216 stimulation cycles recruited from a Taiwan’s reproductive center during 2016-2020. Main outcomes were the numbers, quality of retrieved oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Letrozole inhibits estrogen synthesis, and clomiphene competitively binds estrogen receptors, both of which reduce estrogen levels, increase follicle-stimulating hormone (FSH) release, and promote follicular development. This low estrogen status increases the risk of pregnancy loss or multiple pregnancies [ 6 ]. Secondly, the continuous stimulation of multiple follicles will induce the occurrence of follicular hyperstimulation syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Letrozole inhibits estrogen synthesis, and clomiphene competitively binds estrogen receptors, both of which reduce estrogen levels, increase follicle-stimulating hormone (FSH) release, and promote follicular development. This low estrogen status increases the risk of pregnancy loss or multiple pregnancies [ 6 ]. Secondly, the continuous stimulation of multiple follicles will induce the occurrence of follicular hyperstimulation syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective study evaluated pregnancy rates for mild stimulation with the co-administration of CC and letrozole among POSEIDON Group 4 patients receiving IVF treatment. They showed that patients receiving mild stimulation with the co-administration of CC and letrozole (study group) had higher successful pregnancy rate compared to those for patients receiving COS (control group) despite the higher age and lower baseline AMH [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that both letrozole and clomiphene could increase the release of gonadotropin-releasing hormone (GnRH) by affecting the feedback regulation of GnRH release by estrogen, thereby reducing the use of gonadotropins (Gn) in ART patients [ 4 , 5 ]. Therefore, mild stimulation protocols [ 6 ], including letrozole or clomiphene, are increasingly used in the process of ART because of their good efficacy and relatively low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that mild stimulation protocols could significantly increase the proportion of high-quality oocytes in patients with DOR [ 5 ]. Researchers are still uncertain whether dual trigger can improve the reproductive outcomes of patients with DOR, especially patients undergoing in vitro fertilization (IVF) treatments via mild stimulation protocols.…”
Section: Introductionmentioning
confidence: 99%